Analisis Pengaruh Efek Januari Dan April Terhadap Kinerja Saham Perusahaan LQ 45 - Shinta, Dayu Renanda; Komalasari, Agrianti; Lukman, Iing (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2024)
Purpose : The purpose of this research is to determine the influence between the January Effect and April Effect on Stock Returns.Research Methodology : Researchers collected secondary data using financial data on companies listed in the LQ 45 Index. The data was tested using Eviews 9 software and Microsoft Excel 2010 software.Results : The results of this research indicate that the effect of January and April has no influence on stock returns. The events that happened during the research did not influence stock returns, the events that happened were the general election, the covid 19 virus and the excitement of the new year.Limitations : Researchers cannot approach the object of research because the data taken comes from the IDX and the number of samples is small because companies that have been selected have remained consistent for 5 years of research.Contribution : This research contributes to investors who will invest their funds through companies listed on the LQ 45 index, that the time of buying or selling shares has no influence on stock returns. Because the existing companies are the 45 best companies.Novelty : The use of January and April effects as independent variables in this study has never been done by previous researchers.